2019
DOI: 10.5607/en.2019.28.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism in the Brain and Its Association with Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most progressive neurodegenerative disorder of the aging population after Alzheimer’s disease (AD). Defects in the lysosomal systems and mitochondria have been suspected to cause the pathogenesis of PD. Nevertheless, the pathogenesis of PD remains obscure. Abnormal cholesterol metabolism is linked to numerous disorders, including atherosclerosis. The brain contains the highest level of cholesterol in the body and abnormal cholesterol metabolism links also many neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 140 publications
(151 reference statements)
8
88
0
1
Order By: Relevance
“…It has been speculated that this loss underlies neuronal dysfunctions and the cognitive deficits present at this stage of life [ 41 , 42 , 43 ]. It has also been surmised that dysregulation of cholesterol metabolism is a major factor in neurological diseases accompanied by cognitive dysfunction, such as Alzheimer disease [ 44 , 45 ] (reviewed in [ 23 ]), Parkinson disease [ 46 ], and Huntington disease [ 47 ]. Epidemiological studies have suggested that individuals treated with statins have a lower risk of developing Alzheimer disease [ 25 , 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that this loss underlies neuronal dysfunctions and the cognitive deficits present at this stage of life [ 41 , 42 , 43 ]. It has also been surmised that dysregulation of cholesterol metabolism is a major factor in neurological diseases accompanied by cognitive dysfunction, such as Alzheimer disease [ 44 , 45 ] (reviewed in [ 23 ]), Parkinson disease [ 46 ], and Huntington disease [ 47 ]. Epidemiological studies have suggested that individuals treated with statins have a lower risk of developing Alzheimer disease [ 25 , 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as mentioned, there are neurodegenerative diseases for which a contribution of impaired cholesterol metabolism to the disease has been proposed. For PD, several reports also indicated lysosomal system dysfunction associated with the pathogenesis of PD [143]. Of note, alteration in cholesterol metabolism has been found in PD patient-derived fibroblasts [144] and in the serum lipid profile of PD patients [145,146].…”
Section: Soluble Epoxide Hydrolase In Parkinson's Diseasementioning
confidence: 99%
“…Honokiol (5,3 -diallyl-2,4 -dihydroxybiphenyl) [153,160] 12-(3-(adamantan-1-yl)ureido)dodecanoic acid (AUDA) [92,96] 1,3-bis (4-methoxybenzyl)urea (MMU) [159] N-(1-acetylpiperidin-4-yl)-N-(adamant-1-yl)urea (APAU) [170] (4-(5-phenyl-3-{3-[3-(4-trifluoromethyl-phenyl)-ureido]-propyl}-pyrazol-1-yl)-benzenesulfonamide) (PTUPB) [143] 1-((1-Propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy) phenyl)) urea (TPPU) [109] Funding: This study was supported by the Ministerio de Economía, Industria y Competitividad (Agencia Estatal de Investigación, AEI) and Fondo Europeo de Desarrollo Regional (MINECO-FEDER) (Projects SAF2017-82771-R, SAF2016-33307, RTI2018-096429-B-100). C.G.-F., S.V., C.S., and M.P.…”
Section: Chemical Structure Referencementioning
confidence: 99%
“…Mutations in genes involved in the MVA pathway or cholesterol metabolism, cause neurologic and psychiatric diseases such as Smith–Lemli–Opitz syndrome (SLOS), Niemann-Pick type C disease (NPC), and desmosterolosis [ 26 ]. However, other brain diseases have been related to MVA/cholesterol metabolism such as Autism spectrum disorder (ASD) [ 2 ], Huntington’s disease (HD) [ 29 , 45 ], Alzheimer’s disease (AD) [ 27 , 46 , 47 , 48 ], and Parkinson disease (PD) [ 49 ]. Interestingly, most of them display sex-related differences either on the incidence or severity of symptoms, such as NPC [ 50 , 51 ], AD [ 52 , 53 , 54 ], ASD [ 55 , 56 , 57 ], PD and HD [ 58 ].…”
Section: Cholesterol Metabolism In the Brain: What About Sex And Amentioning
confidence: 99%